ANALYSIS OF MARKETING ASPECT IN FEASIBILITY STUDY OF ASIAN CULTURE GALLERY IN WEST JAKARTA - Nova Sitorus; Juliana Juliana; Chaterine Kho (Universitas Terbuka, 2021)
Based on the data and explanation above, the writer decided to make a business feasibility study from the marketing aspect of an art gallery. The art gallery that will be discussed in this business feasibility study is entitled Asian Culture Gallery. The Asian Culture Gallery, located in West Jakarta, is an art gallery that displays various paintings and explanations of traditional culture, such as traditional dances, special foods, official languages ​​and also traditional clothing from various countries in Asia. These countries include South Korea, Japan, Indonesia, India and the Middle East. In order to produce supporting data, reliable data sets and sources are needed. Therefore, the data obtained must be valid and reliable data. The business feasibility study of the Asian Culture Gallery located in West Jakarta collects data using scientific methods, namely primary data and secondary data. This art gallery will also display some examples of paintings, information and products from the country concerned. The Asian Culture Gallery questionnaire has been distributed online to 153 respondents to find out market interest and responses to questions or statements given. From a market perspective, this gallery is worth running. Keyword: Market, Feasibikity, Gallery, Business